Review of: Barbara Sassi. 2017. “DYRRACHIUM III. Storia e archeologia di una città portuale tra Oriente e Occidente” - Enrico Giorgi (Groma, 2017)
Barbara Sassi. 2017. DYRRACHIUM III. Storia e archeologia di una città portuale tra Oriente e Occidente, Bari: Edipuglia.